1)2х=14-2
2х=12
х=6
2)2х-х=1+3
х=4
3)45-5=3х+2х
5х=40
х=8
4)9х-5х=2+32
4х=34
х=8,5
5)4х-7=2х-3
4х-2х=-3+7
2х=4
х=2
6)8х-3=х+11
8х-х=11+3
7х=14
Пошаговое объяснение:
х=10/3
х=49/3
у=25
х=3
х=5
х=-1
- (14 -21x) = 56; -21x=-56-14; -21х=-70; х=10/3
7(x + 7) = 10x; 7х+49=10х; 7х-10х=-49; -3х=-49; х=49/3
3(x +8) - 3x не указал чему равно это неравенство
(45 - у) + 8 = 28; 45-у+8=28; 53-у=28; у=25
5(x - 5) = - 8x +1; 5х-25=-8х+1; 13х=26 ;х=2
2x = 18 - х; 2х+х=18; 3х=18; х=6
9x + 4 = 48 - 2x; 9х+2х=48-4; 11х=44; х=4
7x+ 3 = 30 - 2x; 7х+2х=30-3; 9х=27; х=3
7 - 2x = 3x - 18; -2х-3х=-18-7; -5х=-25; х=5
0,4x + 3,8 = 2,6 - 0,8x; 0,4х+0,8х=2,6-3,8; 1,2х=2,6-3,8; 1,2х=-1,2; х=-1
1)2х=14-2
2х=12
х=6
2)2х-х=1+3
х=4
3)45-5=3х+2х
5х=40
х=8
4)9х-5х=2+32
4х=34
х=8,5
5)4х-7=2х-3
4х-2х=-3+7
2х=4
х=2
6)8х-3=х+11
8х-х=11+3
7х=14
х=2
Пошаговое объяснение:
х=10/3
х=49/3
у=25
х=2
х=6
х=4
х=3
х=5
х=-1
Пошаговое объяснение:
- (14 -21x) = 56; -21x=-56-14; -21х=-70; х=10/3
7(x + 7) = 10x; 7х+49=10х; 7х-10х=-49; -3х=-49; х=49/3
3(x +8) - 3x не указал чему равно это неравенство
(45 - у) + 8 = 28; 45-у+8=28; 53-у=28; у=25
5(x - 5) = - 8x +1; 5х-25=-8х+1; 13х=26 ;х=2
2x = 18 - х; 2х+х=18; 3х=18; х=6
9x + 4 = 48 - 2x; 9х+2х=48-4; 11х=44; х=4
7x+ 3 = 30 - 2x; 7х+2х=30-3; 9х=27; х=3
7 - 2x = 3x - 18; -2х-3х=-18-7; -5х=-25; х=5
0,4x + 3,8 = 2,6 - 0,8x; 0,4х+0,8х=2,6-3,8; 1,2х=2,6-3,8; 1,2х=-1,2; х=-1